The Fiqh Paradigm for the Pancasila State: Abdurrahman Wahidâs Thoughts on Islam and the Republic of Indonesia - Rochmat, Saefur (Al-Jamiah Research Centre, 2014)
The Republic of Indonesia was not established as a purely secular state as muslims constitute the majority of Indonesians. Indeed, they were divided into three main paradigms: secular, theocratic, and fiqh. The Pancasila state was the result of a gentlemenâs agreement amongst different muslim groups with different paradigms. The regimes of Soekarno and Soeharto considered that the Pancasila state was unique to the Indonesian character and accordingly these leaders tried to unify these different paradigms following Prof Soepomoâs idea of an integralistic state in which the state gives more power to the executive. This idea of an integralistic state is, however, alien to the secular, theocratic, and fiqh paradigms so that this failed to resolve the conflict. In this regard, Abdurrahman Wahid tries to resolve the ideological conflict by incorporating modern sciences into the fiqh paradigm. This fiqh paradigm has supported the establishment of the Republic of Indonesia, but also, according to Wahid, is able to harmonize secular and Islamic aspirations in the national political system.[Republik Indonesia tidak didirikan berdasarkan konsep murni sebuah negara sekuler karena muslim merupakan mayoritas rakyat Indonesia. Muslim Indonesia terbagi dalam tiga paradigma utama: sekular, teokratik, dan fikih. Bentuk negara Pancasila merupakan hasil kesepakatan ketiga kelompok paradigma tersebut. Regime Soekarno dan Soeharto memahami Negara Pancasila sebagai budaya asli bangsa Indonesia dan mereka berusaha menyatukan pendukung ketiga paradigma itu berdasarkan konsep negara integralistic yang diperkenalkan oleh Prof. Soepomo. Namun konsep negara integralistik ini tidak dikenal dalam ketiga paradigm itu, sehingga gagal menyelesaikan konflik. Dalam hal ini Abdurrahman Wahid berusaha menyelesaikan konflik ideologis dengan cara mengadaptasi pengetahuan modern ke dalam paradigma fikih. Paradigma fikih tidak hanya mendukung berdirinya Republik Indonesia, tetapi juga mampu mengharmoniskan aspirasi sekular dan religius dalam sistem politik nasional.]